THE POSITION OF SUPREME COURT REGULATION NUMBER 5 OF 2019 REGARDING GUIDELINES FOR ADDITIONING APPLICATIONS FOR MARRIAGE DISPENSATION POST THE REVISION OF THE MARRIAGE LAW - Astiti, Ni Nyoman Adi; Tarantang, Jefry (UNISSULA, 2022)
The birth of Supreme Court Regulation Number 5 of 2019 concerning Guidelines for Trialing Applications for Dispensation of Marriage is certainly a legal instrument as a means of achieving justice, certainty and benefits for justice seekers, especially as a condition for marriage under the minimum age limit for marriage after the revision of the marriage law. The purpose of this study is to examine the position of Supreme Court Regulation Number 5 of 2019 concerning Guidelines for Trialing Applications for Dispensation of Marriage. This research uses normative method. The background findings of Supreme Court Regulation Number 5 of 2019 concerning Guidelines for Trying Marriage Dispensation Applications to complete the legal vacuum after the revision of the Marriage Law in providing a legal umbrella for the process of adjudicating applications for marriage dispensation which so far have not been clearly regulated in laws and regulations. Position of Supreme Court Regulation Number 5 of 2019 Regarding Guidelines for Adjudicating Applications for Marriage Dispensation, judges must ensure that children's statements are heard in court as an effort to prevent violations of children's rights.